Comparison of efficacy of oral paracetamol versus ibuprofen for PDA closure in preterms – a prospective randomized clinical trial. (2nd May 2020) - Balachander, Bharathi; Mondal, Nivedita; Bhat, Vishnu; Adhisivam, Bethou; Kumar, Mahesh; Satheesh, Santhosh; Thulasingam, Mahalakshmi
Abstract: Background: Currently nonselective cyclooxygenase (COX) inhibitors, ibuprofen and indomethacin, are approved drugs for closure of patent ductus arteriosus but have potential toxicities. There are reports of the effectiveness of paracetamol in ductal closure. However, there is paucity of data comparing paracetamol to ibuprofen or indomethacin in relation to the efficacy and safety profile. Methods: This randomized clinical trial was done in our tertiary care neonatal unit from October 2014 to January 2016 after clearance from ethical committee. It was registered with clinical trial registry of India (CTRI/2016/09/007261) and drug controller general of India (CT/Drugs/56/2014). Preterm neonates with clinical suspicion of hemodynamically significant PDA after echo confirmation were included in the study. Randomization was done by stratified randomization through sealed opaque envelopes. A sample size of 150 was estimated with an expected difference in success of closure as 20% between the treatment groups at level of 5% significance and 80% power. The echocardiography was done 24 hours after completion of treatment by a cardiologist blinded to treatment. Results: The baseline parameters were comparable between two groups. One hundred and forty-six babies had hs-PDA, out of which 110 babies were randomized. No significant difference was found between the two groups with respect to PDA closure (RR 0.97, 95%CI 0.78–1.20, p = 1), mortality or cardio-respiratory morbidity. The babies who received ibuprofen had a higher occurrence of acute kidney injury (RR 0.33, 95%CI 0.13-0.85, p = 0.024). Conclusions: Paracetamol is as effective as ibuprofen for PDA closure in preterm neonates. Ibuprofen used for PDA closure in preterms poses an increased risk for acute kidney injury compared to paracetamol.